The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3390/pathogens10091202
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Prevalence of Mycoplasma hyopneumoniae and Other Respiratory Pathogens in Peri-Weaned, Post-Weaned, and Fattening Pigs with Clinical Signs of Respiratory Diseases in Belgian and Dutch Pig Herds, Using a Tracheobronchial Swab Sampling Technique, and Their Associations with Local Weather Conditions

Abstract: Besides Mycoplasma hyopneumoniae (M. hyopneumoniae), many other viruses and bacteria can concurrently be present in pigs. These pathogens can provoke clinical signs, known as porcine respiratory disease complex (PRDC). A sampling technique on live animals, namely tracheobronchial swab (TBS) sampling, was applied to detect different PRDC pathogens in pigs using PCR. The objective was to determine prevalence of different PRDC pathogens and their variations during different seasons, including correlations with lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 60 publications
(98 reference statements)
3
8
0
Order By: Relevance
“…Furthermore, the swIAV viral loads were the highest at the nursery stage, suggesting that swIAV is present at an early age. This was confirmed in recent studies in Europe ( 16 , 28 ). Hence, swIAV might significantly impact the further clinical course of other pathogens ( 10 , 32 , 33 ).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Furthermore, the swIAV viral loads were the highest at the nursery stage, suggesting that swIAV is present at an early age. This was confirmed in recent studies in Europe ( 16 , 28 ). Hence, swIAV might significantly impact the further clinical course of other pathogens ( 10 , 32 , 33 ).…”
Section: Discussionsupporting
confidence: 86%
“…However, this does not imply that PCV-2 infections do not contribute to respiratory disease and/or PRDC. In addition, its identification is thought to be age-dependent, as an increase from 11% (6- to 11-week-old pigs) to 27% (12- to 25-week-old pigs) was observed in Belgian TBS samples ( 16 ). To ensure its relevance, lymph nodes and/or lung tissues of pigs should be collected to determine PCV-2 infections via immunohistochemistry and qPCR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason of the lower growth rate for 2021–2022 might be attributed to the lower sample size in 2022 as only the first half of the year was tested. Also, since PCVs prevalence is the highest mainly in winter after weaning ( 36 ), the incidence rate in spring 2022 cannot fully reflect the infection rate in that region. In addition, some studies have reported higher rates of infection and more pronounced clinical symptoms of PCV3 when other viruses are present, including PCV2, porcine parvovirus (PPV), and PRRSV ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…bronchiseptica are frequently detected in cases of PRDC [ 12 , 14 , 15 , 16 , 17 ]. However, the type of combinations and kind of associated infectious agents vary with local weather conditions, region, and breeding conditions, which generally complicates the severity, prevention, and control of the disease [ 18 ]. P. multocida is one of the most common bacterial agents isolated from respiratory clinical cases worldwide and often is a secondary or opportunistic pathogen of PRDC [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%